Skill-Differentiated TPACK Enactment and Its Challenges among English Teachers: A Case Study - Bela Bestari; Aminah; Mukrim (Darul Yasin Al Sys, 2026)
Although schools are increasingly equipped with digital facilities, adequate infrastructure does not necessarily ensure meaningful technology integration in English language classrooms, particularly across different language skills. This study examines how three English teachers at a technology-equipped private junior high school in Palu enacted Technological Pedagogical and Content Knowledge (TPACK) and identifies the challenges constraining its implementation. A qualitative case study design was employed, with data collected through nine classroom observations and semi-structured interviews. The data were analyzed through data condensation, data display, and conclusion drawing, using the TPACK framework and Ertmer’s two-order barrier model as deductive coding categories. The findings reveal that TPACK enactment varied across language skills. Teachers selected technology purposefully in writing and reading lessons but relied predominantly on convenience-based choices in speaking lessons, where technology integration was weakest. Technology generally served as pedagogical support rather than as a structurally essential component of instruction, with only one of the nine observed lessons demonstrating fully integrated TPACK. First-order barriers were largely absent because the school provided sufficient infrastructure, whereas second-order barriers arose from teachers’ limited technological repertoire and difficulties in designing technology-based assessments rather than from negative attitudes toward technology. An additional constraint not fully captured by Ertmer’s framework involved students’ inconsistent access to devices and limited familiarity with digital applications. The study concludes that infrastructural adequacy alone does not guarantee integrated TPACK enactment. These findings extend understanding of skill-specific technology integration in English language teaching and imply that teacher professional development should prioritize the expansion of technological repertoires and technology-based assessment capabilities. They also suggest that existing barrier models should incorporate classroom-level constraints related to students’ access and digital competence.